A comparative study of conventional endoscopy and chromoendoscopy for detection of premalignant gastric lesions using methylene blue stain - Athavale, Virendra S.; Nirhale, D. S.; Sonawane, Tejas R.; Chavan, Shahaji G.; Dhande, Mansi S.; Kulkarni, Gaurav C. (International Surgery Journal, 2018)
Background: Early diagnosis represents the most important measure to decrease gastric cancer mortality. Endoscopists should be trained to perform standardized extremely rigorous observation with a low threshold of suspicion for neoplasia. Objective of present study was to compare the efficacy of conventional endoscopy with chromoendoscopy for the detection of gastric premalignant lesions using methylene blue. Methods: 100 cases where enrolled in present study with chronic abdominal pain more than 6 months. All patients underwent conventional endoscopy followed by chromoendoscopy. Biopsies from pylorus, body and fundus were sent for HPE. Comparative study was done between biopsies from conventional endoscopies and chromo endoscopies, Inference (sensitivity, specificity and accuracy) were drawn. Results: Out of 100 patients, 4 of the patients were positive for pre-gastric malignancy. Total 4 biopsies were positive from pylorus of which 1 biopsy was positive by conventional endoscopy and 3 were positive from chromoendoscopy. In our study sensitivity of chromoendoscopy for detection of lesions in pylorus was 25%, specificity was 100% and accuracy was 97%P=0.04 Conclusions: Chromoendoscopy is superior to conventional endoscopy in detection of pre-gastric malignancy. Chromoendoscopy could be performed in the same setup of conventional endoscopy which was relatively cheaper than the other modalities and the results were equivocal with that of other commercial modalities.